MENTAL TOUGHNESS IN VOLLEYBALL ATHLETES: ANALYSIS BY PLAYING POSITION, ACHIEVEMENT LEVEL, AND GENDER - Filda Syafira Razanah; Miftakhul Jannah; Damajanti Kusuma Dewi (Jambura Health and Sport Journal, 2026)
This study aims to analyze differences in mental toughness among volleyball athletes based on playing position, performance achievement level, and gender, including the interactions among these factors. A quantitative approach with a descriptive-comparative and cross-sectional design was employed. The sample consisted of 320 male and female volleyball athletes in East Java, selected using purposive sampling. Mental toughness was measured using the Mental Toughness Inventory (MTI) with a four-point Likert scale, comprising 24 valid items with high reliability (Cronbach’s α = 0.967). Data were analyzed using a Three-Way Analysis of Variance (ANOVA) after meeting the assumption of homogeneity of variance. The results showed no significant main effects of performance achievement level (p = 0.592), gender (p = 0.179), or playing position (p = 0.094) on mental toughness. The interactions between performance achievement level and gender, performance achievement level and playing position, gender and playing position, as well as the three-way interaction were also non-significant, with all eta-squared values falling within the very small effect category (Cohen, 1988). These findings indicate that mental toughness levels among the volleyball athletes in this study were relatively similar across performance achievement level, gender, and playing position, with no evidence of significant interactions among these three characteristics.